STRATEGI KAMPANYE NON KOMERSIL DALAM ILMU KOMUNIKASI UNTUK MEMBANGUN KESADARAN PUBLIK - Harahap, Delvira Nurul Aini Yuliandari (Sintesa, 2025)
Social media has become a very effective communication platform in conveying messages to a wide and fast audience. In the context of non-commercial campaigns, social media offers a great opportunity for organizations and individuals to raise public awareness of social, environmental, health and other issues at relatively low cost. Social media allows the dissemination of information in real-time and reaches audiences in various regions without requiring large costs. The findings of this research show that Indonesia has a very high number of social media users, making social media an ideal platform for implementing non- commercial campaigns. This research uses a qualitative approach with data collection methods in the form of case studies, interviews and content analysis. The aim of this research is to analyze non-commercial campaign strategies in the field of communication science, with a focus on the use of social media, influencer involvement, and the application of attractive visual content to build public awareness. The research results show that an effective campaign strategy involves creating content that is not only informative but also emotional and relevant, capable of arousing audience attention and empathy. Additionally, audience engagement through active interactions on social media, such as comments, content sharing, or participation in online activities, has been proven to significantly increase the impact of campaigns. The use of strong visuals, such as images, videos or infographics, plays an important role in attracting attention and making it easier to convey messages. On the other hand, the involvement of influencers who have many fans who are able to convey the campaign message well is also a key factor in expanding the reach and effectiveness of the campaign. This research concludes that planned, creative and relevant strategies make social media a very effective tool in building public awareness while encouraging active community participation on important issues. Keywords: Social Media, Campaign, Influencer, Communication Science, non-commercial